TECHNOLOGIES FOR THE DEVELOPMENT OF CRITICAL THINKING IN PRIMARY SCHOOL STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This thesis covers issues of the development of critical thinking in the primary education system, methods of applying critical development technologies, forms and principles of the development of critical thinking, actions for the formation of critical thinking, stages and activities of critical thinking of students, methods called "Correct statements" and “Monitoring Journal”.